Persistence in the Variability of Daily Exchange Rates - Tsibouris, George (IMF Working Papers; Working Paper ;, 1991)
Rational speculation in foreign exchange trading is often assumed to dampen exchange rate fluctuations by bringing the market back to fundamentals. Nevertheless, information congestion provides incentives for traders to follow positive feedback strategies which result in persistent and volatile exchange rate behavior by magnifying the impact of exogenous shocks. Empirical evidence is presented which is consistent with such autocatalytic effects.